Ulnar Goniometer: a simple device for better neurophysiological evaluation of the Motor Conduction Velocity of the Ulnar Nerve. - Gallicchio, Lara; Recchia, Valentina Rachele; Didonna, luigi; Vecchio, Eleonora; Guida, Piero; Petruzzellis, Antonella; Tamma, Filippo (Journal of Biomedical Practitioners, 2022)
OBJECTIVE The use of the Ulnar Goniometer standardizes the method of detecting the Motor Conduction Velocity (MCV) of the Ulnar nerve by keeping the elbow flexed at a fixed angle, thus enabling an easier and more precise measurement. MATERIALS AND METHODS The stimulations were performed by two independent operators. We evaluated 30 participants of both genders with paresthetic symptoms of the upper limbs and 30 healthy and asymptomatic volunteers. Each operator performed the examination without and with the use of the Ulnar Goniometer, detecting the velocity of motor conduction wrist-below elbow and the speed above-elbow (AE) below-elbow (BE). Agreement between the measurements was assessed with intraclass correlation coefficient (ICC). RESULTS The repeatability of the measurements between operators was modest without the use of the support (ICC = 0.152) while a good agreement was found when the operators used the support (ICC = 0.499). DISCUSSION AND CONCLUSIONS The most obvious results of the study were the reduction of the difference between operators using the Ulnar goniometer, the increase in the repeatability of the measurements and the specificity of the test.